From bureaucracy to humanocracy: Role of leadership - Golandaz, Hafiza (2005)
The article defines bureau-neurosis as the degenerated form of bureaucracy which fails to provide individuals with harmony at work place, autonomy and participation in decision-making, informalness in relationships and above trust in organisation. This negation of fundamental emotional needs - to be understood and to be treated with respect - leads to discord in the organisations. Hence it is in the interest of both the individuals as well as organisations that such bureau-neurosis is not created in the first place. Incorporation of he principles of humanocracy in the working of bureaucracy is, therefore, recommended as a preventive mechanism. - Reproduced.
Keywords: Leadership; Bureaucracy